2014
DOI: 10.1590/s2317-15372014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and physiological changes of Tabebuia roseoalba (Ridl.) Sandwith (Bignoniaceae) seeds under storage

Abstract: -Tabebuia roseoalba (Ridl.) Sandwith is a Brazilian forest species, with great use in landscaping and reforestation, occurring mainly in the semi-deciduous forest. Seeds are small, lightweight, winged and wind-dispersed. The objective of this study was to verify the physiological quality and biochemical changes in T. roseoalba seeds during 24-month storage. The following were assessed: germination, emergence, seedling length and seedling dry weight, content of lipids, proteins and phenolic compounds, and enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…As a consequence, the number of cells in division and the mitoctic index may be affected, as observed in Triticum aestivum seeds (Menezes et al, 2014). In Tabebuia roseoalba seeds, a reduction in physiological quality of the seeds was observed, brought about by storage, with reduction in protein levels (Abbade and Takaki, 2014). Accelerated aging provides a favorable condition to seed deterioration, similar to storage.…”
Section: Accelerated Aging In Mobilization Of Reserves During Germinamentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the number of cells in division and the mitoctic index may be affected, as observed in Triticum aestivum seeds (Menezes et al, 2014). In Tabebuia roseoalba seeds, a reduction in physiological quality of the seeds was observed, brought about by storage, with reduction in protein levels (Abbade and Takaki, 2014). Accelerated aging provides a favorable condition to seed deterioration, similar to storage.…”
Section: Accelerated Aging In Mobilization Of Reserves During Germinamentioning
confidence: 99%
“…Nevertheless, mobilization undergoes the effect of osmotic components (Reis et al, 2012), of salinity (Silva et al, 2008;Dantas et al, 2014), of light and growth regulators (Ren et al, 2007;Zanotti et al, 2014), of accelerated aging (Zhu and Chen, 2007;Menezes et al, 2014), and of storage (Abbade and Takaki, 2014), factors which may accelerate or slow the process, as well as hurt the development of normal seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…During seed storage, some alterations in the levels of biomolecules such as carbohydrates (Bernal-Lugo and Leopold 1992;Garcia et al 2006;Hellmann et al 2008;Veselova et al 2015) and amino acids (Sasaki et al 2013) can occur. Some studies have shown that changes in these compounds during seed storage may be associated with a loss of seed viability (Chandrashekar 2012;Sasaki et al 2013;Abbade and Takaki 2014;Veselova et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, the rapid loss of seed vigor was due to the increase in water content during storage, a fact that was not verified for "mofumbo" seeds. Similarly, Abbade and Takaki (2014) with Tabebuia roseoalba seeds also found that the storage period significantly compromised germination, decreasing from 88% to 14% at the end of 24 months. The germination speed index indicated a reduction in the vigor of "mofumbo" seeds during storage.…”
Section: Resultsmentioning
confidence: 83%